Appraising rice consumption pattern in India: trends, preferences and food security - Pradhan, Asit Kumar; Mondal, Biswajit; Bisen, Jaiprakash; Jambhulkar, NN; Kumar, GAK; Mishra, SK (ORYZA-An International Journal of Rice, 2023)
Rice is one of the most important crops of South Asian countries especially in India, China, and Bangladesh in which rice is consumed in larger quantity than other cereals as well as other food items. With increase in population though total consumption of rice had increased, per capita consumption had shown a decreased trend in recent years due to change in the dietary pattern of consumers. In this paper it has shown that how the rice consumption has been changed in India as well as in different states of the country. Further it has been studied for consumption of rice in rural and urban regions of the country and calories intake from rice as compared with other cereals as well as non-cereal items. Contribution of rice in the food security and the consumer preference according to certain prior characteristics like taste, quality of grain, aroma, etc. has been discussed in this paper.